2022
DOI: 10.1186/s13102-022-00435-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 restrictions on Australians' frequency and duration of participation in different types of sport and physical activity

Abstract: Background Sports management and public health physical activity stakeholders need to understand changing patterns of participation to inform the development of sport and physical activity opportunities and strategies. This study investigated changes in the frequency and duration of participation in sport and physical activity in Australia from pre-COVID-19 to during-COVID-19, broken down by the specific type of activity and by gender, age and region. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The impact of COVID-19 on participation in sport and physical activity in general in uenced various demographic groups differently. For example, the largest decline in participation in community sport in Australia was for those aged 4-9 years, and the decline was greater for females than males (11). The gender differences reported for participation in sport are similar to those from other studies on leisuretime physical activity which reported greater declines in participation during COVID-19 restrictions for females (12).…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…The impact of COVID-19 on participation in sport and physical activity in general in uenced various demographic groups differently. For example, the largest decline in participation in community sport in Australia was for those aged 4-9 years, and the decline was greater for females than males (11). The gender differences reported for participation in sport are similar to those from other studies on leisuretime physical activity which reported greater declines in participation during COVID-19 restrictions for females (12).…”
Section: Introductionsupporting
confidence: 77%
“…Similarly, in a Korean study, participation in indoor activities such as bodybuilding and swimming decreased whilst outdoor activities including climbing and cycling increased (10). Overall, community sport participation in Australia declined by 27% in 2020 compared to pre-COVID levels (11). I…”
Section: Introductionmentioning
confidence: 95%
“…However, all levels of government, government agencies and sport organisations need to understand that the way in which many people want to consume and play sport is more diverse than being channelled into organised competition structures. Changing patterns of participation have been developing over the past couple of decades, and perhaps COVID-19 has been the "perfect storm" for stakeholder organisations to reassess, develop and implement a new model of sport (4). In order to consider what a new model of sport would look like, we first need to summarise what are the most important motivators for people to participate in sport.…”
Section: The Broader Needs Of Participants -Key Influencing Factorsmentioning
confidence: 99%
“…Whilst children's participation in sport is largely through a local sport club or association, adults who play sport are much less likely to do so within a club-based setting because more flexible and less competitive options seem to be preferred by many adults (3). Also, organised sport is increasingly being offered by various private and public organisations that are not sport clubs (4).…”
Section: Introduction the Origins Of Club-based Sportmentioning
confidence: 99%
“…The European Parliament resolution of 10 February 2021 on the impact of COVID-19 on youth and on sport stressed that "the COVID-19 pandemic is having devastating consequences on the entire sports sector at all levels, especially on sporting organisations and clubs, leagues, gyms and fitness centres, athletes, coaches, staff, and sport-related business, including sports event organisers and sports media; considers that the road to recovery will be challenging and underlines the need for targeted relief measures" [10]. The devastating effect of COVID-19 pandemic on various aspects of sport and athletes at all levels and types of sport was also observed outside of Europein Australia [9], Japan [18], USA [19], Brazil [13], South Africa [25], Turkey [29] and other countries [14]. Haan et al [14] analyzed both physical and mental effects of the COVID-19 pandemic and the imposed restrictions and regulations on athletes in soccer, hockey, rugby, cricket, athletics, netball, basketball, handball, endurance running, cycling, track and field, swimming, squash, golf, tennis and karate.…”
Section: Introductionmentioning
confidence: 99%